Severe COVID-19 disease in a 2nd trimester pregnancy: Successful ECMO and mechanical ventilation management. (2022) - Hansra, Barinder S.; Rao, Vidya K.; Vogelsong, Melissa A.; Ruoss, Stephen J.
Abstract: Extracorporeal membrane oxygenation (ECMO) is an invasive support strategy for cardiac, respiratory, or combined cardiorespiratory failure. ECMO has become increasing utilized in patients with severe respiratory failure due to COVID-19 infection. To our knowledge there is no report of successful ECMO utilization in second trimester of pregnancy leading to a successful outcome. We present a case of severe COVID-19 infection in a patient causing respiratory failure in the second trimester pregnancy. With diligent utilization of ECMO and mechanical ventilation we were able to support the patient's respiratory needs to allow her pregnancy to continue. Ultimately, the patient underwent successful caesarean section in the third trimester. This case highlights excellent lung injury protection and lung recovery can be achieved through optimal utilization of ECMO support together with a careful and closely monitored lung protective ventilation strategy, even while also supporting the patient through the increasing metabolic circumstances of a progressing pregnancy.